CORPORATE ENVIRONMENTAL CONSCIOUSNESS AND COST OF FINANCING: CASE OF INDONESIAN LISTED FIRMS - Ainindita
In the last decade, there has been a growing concern towards corporations that uphold environmental consciousness thus increasing sustainable finance. Literature shows that corporate’s environmental awareness acts such as corporate’s disclosure of sustainability report, carbon emission strategy, and emission have reduced the cost of financing. This is due to environmental awareness is expected to minimize the risk of investing and information asymmetry. However, concerns on similar issues have just raised recently in Indonesia. Thus, this paper aims to examine the evidence in Indonesia and whether by implementing responsible business has reduced the firm’s cost of financing. Examining the sample of KOMPAS 100 firms during the period of 2015-2019, using multi linear regression, and analyzing the sustainability report disclosure, type of emitting industry, emission count, and environment programs to measure environment activities, the researcher finds a negative and significant relationship between environmental carbon emission intensity and type of emitting industries to cost of financing. However, sustainability report disclosure and number of environmental programs are found insignificant. This leads to conclusion that environmental performance is a significant risk factor in valuing cost of financing ( cost of capital, cost of debt, cost of equity), but in valuing the number of environmental programs and sustainability report disclosure, it is required to add more measurements and more proxies to explain firm’s environmental performance.